Public preference towards wasiyyah / Wan Nur Syazwana Wan Ismail - Wan Ismail, Wan Nur Syazwana (2014)
In Islamic distributions of wealth, we have a few methods that can help us to distribute the wealth properly. There are few methods, such as faraid, wasiyyah, hibah, waqf and others, but, for every types of wealth distribution, it has different terms and conditions. In this study, the researcher focuses more on wasiyyah. It is because nowadays wasiyyah is became more famous title that was debating today. The years ago, wasiyyah is unknown method because only few peoples made it. Just like a targeting by Amanah Raya Berhad, the numbers is not achieved, because only few cases was reported there, but today, it became one of the method of distributed of wealth without know the reason. So, the researcher makes a research about this topic. The objective of the researcher is want to examine what the actually cause that peoples today choose wasiyyah as their medium of distribution. In order to implement that objective, the researcher has been distributed the questionnaires in Kuantan. Based on the data collection, she make an analysis, she got that the main reasons is family practices. It is because persons who are make wasiyyah are the persons that concern about family custom, besides want to close the relationship with their family.